Lung clearance index evaluation in detecting nocturnal hypoxemia in cystic fibrosis patients: Toward a new diagnostic tool. (April 2020) - Papale, Maria; Parisi, G.F.; Spicuzza, L.; Licari, A.; Bongiovanni, A.; Mulè, E.; Rotolo, N.; Manti, S.; Leonardi, S.
Abstract: Background: Nocturnal hypoxemia adversely affects outcomes in patients with cystic fibrosis (CF). Although an early detection of this abnormality may be desirable, still its predictability remains uncertain. The Lung Clearance Index (LCI) is a measure of lung ventilation distribution obtained from a multiple-breath washout technique (MBW), recently implemented in patients with CF. This study aimed to establish whether the LCI predicts nocturnal hypoxemia in patients with stable CF, with mild to moderate disease, and normal diurnal gas exchange. Methods: 31 stable patients (15 males, mean age 17.4 ± 5.2 years) with mild to moderate CF, normoxic when awake, were enrolled. In all patients we performed nocturnal cardio-respiratory polygraphy, lung function measurement, and MBW test to derive LCI values. Results: LCI was abnormal in most of the patients and inversely correlated with mean nocturnal SpO2 (r = −0.880 p < 0.01). A receiver operating characteristic (ROC) analysis, performed to assess whether LCI predicted nocturnal hypoxemia, revealed a high predictive accuracy of LCI for nocturnal desaturation (AUC = 0.96; Youden index = 0.79). Forced expiratory volume in 1 s (FEV1 ) was predictive only in patients with more severe airway obstruction, with a moderate degree of accuracy (AUC 0.71). Conclusions: The LCI showed a high effectiveness in predicting nocturnal hypoxemia in stable patients with CF, particularly when compared with a traditional parameter of lung function such as FEV1 . Highlights: Nocturnal hypoxemia adversely affects outcomes in patients with cystic fibrosis. The LCI predicts nocturnal hypoxemia in patients with cystic fibrosis. The LCI detects lung damage more precociously than spirometry.